Activation of the pro-migratory bone morphogenetic protein receptor 1B gene in human MDA-MB-468 triple-negative breast cancer cells that over-express CYP2J2. (November 2016) - Allison, Sarah E.; Chen, Yongjuan; Petrovic, Nenad; Zimmermann, Stefanie; Moosmann, Bjoern; Jansch, Mirko; Cui, Pei H.; Dunstan, Colin R.; Mackenzie, Peter I.; Murray, Michael
Abstract: Secondary metastases are the leading cause of mortality in patients with breast cancer. Cytochrome P450 (CYP) 2J2 (CYP2J2) is upregulated in many human tumors and generates epoxyeicosanoids from arachidonic acid that promote tumorigenesis and metastasis, but at present there is little information on the genes that mediate these actions. In this study MDA-MB-468 breast cancer cells were stably transfected with CYP2J2 (MDA-2J2 cells) and Affymetrix microarray profiling was undertaken. We identified 182 genes that were differentially expressed in MDA-2J2 cells relative to control (MDA-CTL) cells (log[fold of control] ≥2). From gene ontology pathway analysis bone morphogenetic protein (BMP) receptor 1B (BMPR1B) emerged as an important upregulated gene in MDA-2J2 cells. Addition of the BMPR1B ligand BMP2 stimulated the migration of MDA-2J2 cells, but not MDA-CTL cells, from 3D-matrigel droplets. Migration of MDA-2J2 cells was prevented by the BMPR antagonist dorsomorphin. These findings indicate that over-expression of CYP2J2 in MDA-MB-468-derived breast cancer cells activates BMPR1B expression that may contribute to increased migration. Targeting BMPR1B may be a novel approach to inhibit the metastatic activity of breast cancers that contain high levels of CYP2J2.